Relationship between handgrip strength, physical function, and risk of falls in older people - Catalina Rojas; Nelly Venegas; Jaime Vasquez-Gomez; Claudia Troncoso-Pantoja; Yeny Concha-Cisternas (Revista Cubana de Medicina Militar)
Introduction: Handgrip strength is a way to evaluate muscle weakness in older people and it has been seen to show a high correlation with general strength and body muscle mass, which is why it could help in the early detection of deterioration in physical function. loss of lower limb strength and risk of falls. Objective: To relate handgrip strength with physical function and risk of falls in older people. Methods: Descriptive, correlational study. It evaluated 87 older people (24 men and 63 women) between 65 and 75 years old, from 4 social organizations in the city of Talca, Chile, selected through a non-probabilistic convenience sampling. To measure the handgrip strength, a hand dynamometer was used, to assess physical function the Short Physical Performance Battery test was used, and the unipodal station and time up and go tests were used to evaluate balance static and dynamic respectively. Results: Moderately significant relationships were observed between the handgrip strength in the Short Physical Performance Battery test (p = 0.001; r = 0.473) and with all the tests that make up this battery. A moderate one was also evidenced between the grip strength and the unipodal station test (p = 0.001; r = 0.472), while the relationship with the time up and go test was weak inverse (p = 0.002; r = -0.398). Conclusion: There is a relationship between handgrip strength with physical function and the risk of falls in older people. This finding is important because it suggests that handgrip strength could be used in clinical practice as an indirect indicator or as an early detection tool for loss of general strength capacity, physical fitness, and risk of falls.